2016
DOI: 10.1080/11263504.2016.1165752
|View full text |Cite
|
Sign up to set email alerts
|

Circumscription of the South American moonwort Botrychium (Ophioglossaceae)

Abstract: The genus Botrychium (Ophioglossaceae) is comprised of about 30 widely distributed species. Because of their small size and few, yet variable, morphological characters, many questionable taxa have been described over the years. Since its description in 1906, B. dusenii has been treated as both a distinct species and variously divided into four taxa: B. lunaria var. dusenii, B. lunaria var. typicum, B. lunaria var. antarctica, and B. ramosum var. patagonicum (B. matricariaefolium subsp. patagonicum). The aim of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
5
1
Order By: Relevance
“…Maternal contributors of polyploids are shown as green lines and their paternal contributors as violet lines. Uncertainties of parental progenitors-cases where our results either conflict with earlier hypotheses (Farrar, 2011;Gilman et al, 2015;Meza-Torres et al, 2017), or are incongruent between Figs. 1 and 3, or even could be erroneous due to unsampled diploids (Stensvold and Farrar, 2017) ∼160 my from the other fern lineages (Pryer et al, 2004;Rothfels et al, 2015).…”
Section: Recent Rapid Radiation In An Ancient Lineagecontrasting
confidence: 74%
See 1 more Smart Citation
“…Maternal contributors of polyploids are shown as green lines and their paternal contributors as violet lines. Uncertainties of parental progenitors-cases where our results either conflict with earlier hypotheses (Farrar, 2011;Gilman et al, 2015;Meza-Torres et al, 2017), or are incongruent between Figs. 1 and 3, or even could be erroneous due to unsampled diploids (Stensvold and Farrar, 2017) ∼160 my from the other fern lineages (Pryer et al, 2004;Rothfels et al, 2015).…”
Section: Recent Rapid Radiation In An Ancient Lineagecontrasting
confidence: 74%
“…The genus comprises an estimated 48 taxa divided among three major clades: Lanceolatum (3 diploids, 14 polyploids), Lunaria (10 diploids, 1 polyloid), and Simplex-Campestre (11 diploids, 9 polyploids;Dauphin et al, 2017). Previous studies additionally revealed various morphologically cryptic taxa (including both diploids and polyploids) and provided a phylogenetic foundation that helped identify diagnostic morphological characters (Stensvold and Farrar, 2017;Williams et al, 2016;Meza-Torres et al, 2017;Farrar and Gilman, 2017). However, despite the recent advances in our understanding of the maternal phylogenetic relationships among Botrychium taxa, phylogenetic information about the paternal lines through nuclear sequencing is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Dusén's collection, from a single population, was subjected to critical and controversial examination by European botanists, most notably by Christ (1906) . Th e collection was sorted into several putative new taxa [including erroneously, B. matricariifolium (Döll) A.Braun ex W.D.J.Koch] before ultimately becoming recognized as representing a single taxon, Botrychium dusenii (Christ) Alston ( Alston, 1960 ;Meza-Torres et al, 2016 ), although the plants continued to be considered by some European and North American botanists as B. lunaria (L.) Sw. var. dusenii Christ, a variant of circumboreal B. lunaria ( Clausen, 1938 ).…”
Section: Resultsmentioning
confidence: 99%
“…Botrychium dusenii extends down the southern Andes Mountains over 2000 km from approximately 32 ° S to southernmost Tierra del Fuego and in elevation from 2740 m a.s.l. in the north to sea level in Tierra del Fuego and the Falkland Islands ( Meza-Torres et al, 2016 ). Th e South Pacifi c taxon extends over a similar extent from the South Island of New Zealand to southeastern Australia and Tasmania in alpine and subalpine zones above 700 m ( Brownsey and Perrie, 2015 ).…”
Section: Dates Of Dispersals-mentioning
confidence: 99%
See 1 more Smart Citation